On the Driving Forces Behind Cyclical Movements in Employment and Job Reallocation - Davis, Steven J; Haltiwanger, John (American Economic Review, 1999)
Theory restricts short-run job creation and destruction responses and cumulative employment and job reallocation responses to allocative and aggregate shocks. We formulate these restrictions and implement them for postwar data on U.S. manufacturing. Allocative shocks are the main driving force behind cyclical movements in job reallocation, but their contribution to employment fluctuations varies greatly across alternative identification assumptions. Also, the data compel one or both of the following inferences: aggregate shocks greatly alter the shape and not just the mean of the cross-sectional density of employment growth rates; allocative shocks cause short-run reductions in aggregate employment. (JEL C32, E32, J63)